Quantified postsurgical small cell size CTCs and EpCAM+ circulating tumor stem cells with cytogenetic abnormalities in hepatocellular carcinoma patients determine cancer relapse. (1st January 2018) - Wang, Liang; Li, Yilin; Xu, Jing; Zhang, Aiqun; Wang, Xuedong; Tang, Rui; Zhang, Xinjing; Yin, Hongfang; Liu, Manting; Wang, Daisy Dandan; Lin, Peter Ping; Shen, Lin; et al.
Abstract: Detection of hepatocellular carcinoma circulating tumor cells performed with conventional strategies, is significantly limited due to inherently heterogeneous and dynamic expression of EpCAM, as well as degradation of cytokeratins during epithelial-to-mesenchymal transition, which inevitably lead to non-negligible false negative detection of such "uncapturable and invisible" CTCs. A novel SE-iFISH strategy, improved for detection of HCC CTCs in this study, was applied to comprehensively detect, in situ phenotypically and karyotypically characterize hepatocellular and cholangiocarcinoma CTCs (CD45 − /CD31 − ) in patients subjected to surgical resection. Clinical significance of diverse subtypes of CTC was systematically investigated. Existence of small cell size CTCs (≤5 μm of WBCs) with cytogenetic abnormality of aneuploid chromosome 8, which constituted majority of the detected CTCs in HCC patients, was demonstrated for the first time. The stemness marker EpCAM + aneuploid circulating tumor stem cells (CTSCs), and EpCAM − small CTCs with trisomy 8, promote tumor growth. Postsurgical quantity of small triploid CTCs (≥5 cells/6 ml blood), multiploid (≥pentasomy 8) CTSCs or CTM (either one ≥ 1) significantly correlated to HCC patients' poor prognosis, indicating that detection of those specific subtypes of CTCs and CTSCs in post-operative patients help predict neoplasm recurrence. Highlights: SE-iFISH was improved to effectively detect and comprehensively characterize diverse subtypes of CC and HCC CTCs. Existence of small aneuploid HCC CTCs (≤WBCs), and correlation of those small CTCs to clinical outcomes were demonstrated. Postsurgical quantity of EpCAM+ CTSCs, triploid EpCAM − small CTCs and CTMs, highly correlated to HCC recurrence.